2014
DOI: 10.3324/haematol.2013.092643
|View full text |Cite
|
Sign up to set email alerts
|

Sin3a-associated Hdac1 and Hdac2 are essential for hematopoietic stem cell homeostasis and contribute differentially to hematopoiesis

Abstract: Class I histone deacetylases are critical regulators of gene transcription by erasing lysine acetylation. Targeting histone deacetylases using relative non-specific small molecule inhibitors is of major interest in the treatment of cancer, neurological disorders and acquired immune deficiency syndrome. Harnessing the therapeutic potential of histone deacetylase inhibitors requires full knowledge of individual histone deacetylases in vivo. As hematologic malignancies show increased sensitivity towards histone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 54 publications
(78 reference statements)
2
42
1
Order By: Relevance
“…We attribute the surprisingly limited overlap between altered lung transcriptomes of Sin3a LOF and Hdac1/2 LOF embryos to the much earlier developmental defects observed in the former. Sin3a-dependent defects in lung endoderm in our study are consistent with the recent results of Heideman et al (2014) in the hematopoietic system, where Sin3a LOF phenocopied the effects of Hdac1/2 LOF on renewal and differentiation of hematopoietic stem and multipotent progenitor cells. Furthermore, cell type-specific differences in Sin3a function within breast cancer cells, in which estrogen receptor alpha status correlated with Sin3a-dependent tumor growth and survival (Ellison-Zelski and Alarid, 2010), shares similarities with our observation of cell/tissue-specific differences in the requirement for Sin3a within the foregut endoderm.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We attribute the surprisingly limited overlap between altered lung transcriptomes of Sin3a LOF and Hdac1/2 LOF embryos to the much earlier developmental defects observed in the former. Sin3a-dependent defects in lung endoderm in our study are consistent with the recent results of Heideman et al (2014) in the hematopoietic system, where Sin3a LOF phenocopied the effects of Hdac1/2 LOF on renewal and differentiation of hematopoietic stem and multipotent progenitor cells. Furthermore, cell type-specific differences in Sin3a function within breast cancer cells, in which estrogen receptor alpha status correlated with Sin3a-dependent tumor growth and survival (Ellison-Zelski and Alarid, 2010), shares similarities with our observation of cell/tissue-specific differences in the requirement for Sin3a within the foregut endoderm.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have shown that a common effect of the loss of Sin3a expression in stem cells and cancer cells is decreased cell proliferation coupled with increased apoptosis (Ellison-Zelski and Alarid, 2010;Heideman et al, 2014;McDonel et al, 2012). In this study, immunostaining for the apoptotic marker cleaved caspase 3 revealed that there are, albeit very few, apoptotic epithelial cells in …”
Section: Loss Of Sin3a Leads To Specific Lung Developmental Defectsmentioning
confidence: 59%
“…It has been previously shown that inactivation of Sin3A or combined genetic deletion of HDAC1 and HDAC2 results in the drastic loss of hematopoietic cells and loss of HSC viability and repopulation capacity. 37 This phenotype differs from what we observed upon genetic inactivation of Sin3B in the hematopoietic system, leading us to speculate that Sin3A and Sin3B regulate distinct pathways in HSCs. In support of this, Sin3A is unable to compensate for the defects present in Sin3B CKO HSCs despite being expressed in these cells (data not shown).…”
Section: Discussioncontrasting
confidence: 53%
“…SIN3 is a scaffolding protein that was initially identified as a global regulator of gene transcription in yeast, whereas two isoforms have been found in mammals, Sin3A and Sin3B 7,8 . SIN3 proteins can link HDAC and co-repressors to chromatin-bound transcription factors to inhibit target gene expression 9,10 .…”
mentioning
confidence: 99%